Sleep spindles and rapid eye movement sleep as predictors of next morning cognitive performance in healthy middle‐aged and older participants. (18th November 2013) - Lafortune, Marjolaine; Gagnon, Jean‐François; Martin, Nicolas; Latreille, Véronique; Dubé, Jonathan; Bouchard, Maude; Bastien, Célyne; Carrier, Julie
Summary Spindles and slow waves are hallmarks of non‐rapid eye movement sleep. Both these oscillations are markers of neuronal plasticity, and play a role in memory and cognition. Normal ageing is associated with spindle and slow wave decline and cognitive changes. The present study aimed to assess whether spindle and slow wave characteristics during a baseline night predict cognitive performance in healthy older adults the next morning. Specifically, we examined performance on tasks measuring selective and sustained visual attention, declarative verbal memory, working memory and verbal fluency. Fifty‐eight healthy middle‐aged and older adults (aged 50–91 years) without sleep disorders underwent baseline polysomnographic sleep recording followed by neuropsychological assessment the next morning. Spindles and slow waves were detected automatically on artefact‐free non‐rapid eye movement sleep electroencephalogram. All‐night stage N2 spindle density (no./min) and mean frequency (Hz) and all‐night non‐rapid eye movement sleep slow wave density (no./min) and mean slope (μV/s) were analysed. Pearson's correlations were performed between spindles, slow waves, polysomnography and cognitive performance. Higher spindle density predicted better performance on verbal learning, visual attention and verbal fluency, whereas spindle frequency and slow wave density or slope predicted fewer cognitive performance variables. In addition, rapid eye movement sleep duration was associated with better verbal learning potential. These results suggest that spindle density is a marker of cognitive functioning in older adults and may reflect neuroanatomic integrity. Rapid eye movement sleep may be a marker of age‐related changes in acetylcholine transmission, which plays a role in new information encoding.